Study Of Genitalia Morphometric Variability Of The Two Species Helix Aperta And Helix Aspersa (gasteropoda, Pulmonata) - Benbellil Tafoughalt, S.; Bendifallah, L. (University of Eloued جامعة الوادي, 2017)
Our research aims for, firstly, the study of genitalia morphometric variability of the two species Helix aperta and Helix aspersa, and the relation of this variability with individual’s weight and shell size. Secondly, differences in dimensions of the genital organs between the two studied species were investigated. This study showed, first, the existence of an important dimensional variability of genital organs in both studied species, then, a positive correlation between organs’ measurements and those of weight and shell. Finally, two genital organs, that are flagellum and proximal duct of bursa copulatrix, proved to be interesting to discriminate between the two species Helix aperta and Helix aspersa, because both organs are greater in Helix aspersa.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 01
Keywords: Genitalia, Helix aperta, Helix aspersa, morphometric variability, positive correlation, weight, shell size, discriminating characters.